A further note on a new class of solutions to dynamic programming problems arising in economic growth - Jürgen Antony; Alfred Maußner (Universität Augsburg, Institut für Volkswirtschaftslehre, 2008)
This note extends the finding of Benhabib and Rusticchini (1994) who provide a class of SDGE models, whose solution is characterized by a constant savings rate. We show that this class of models may be interpreted as a standard representative agent SDGE model with costly adjustment of capital and provides a solution to the traditional discrete time Ramsey problem.
urn:nbn:de:bvb:384-opus4-711378
Keywords: C61; C68; E21; O4; 330; Capital and labor substitution; Dynamic programming; Growth; Numerical solutions of SDGE models; Dynamische Optimierung; Dynamisches Gleichgewicht; Stochastischer Prozess; Faktorsubstitution; Theorie